1993
DOI: 10.1088/0953-4075/26/18/018
|View full text |Cite
|
Sign up to set email alerts
|

The classical limit of ionization in fast ion-atom collisions

Abstract: The authors study the classical-quantum correspondence for ionization in three-body fast ion-atom collisions. The existence of a classical limit of the quantum mechanical transition probabilities as a function of the momentum transferred to the electron during the collision, the impact parameter, the energy and angle of the emitted electron, and the initial quantum level of the target is investigated. A well behaved classical limit is shown to exist for large momentum transfers whereas ionization by small mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 48 publications
1
53
0
Order By: Relevance
“…Whereas our theoretical results exhibit a very good agreement with the recent calculations of Errea et al for describing the CI process [13], we clearly observe an underestimation of the results reported by Gervais et al in [14] (see Panel c)) for the DI process. This large disagreement is actually not well understood but highlights the limitation of the CTMC approach to treat the DI process as already mentioned by Reinhold and Burgdörfer [26] who have shown that in the IEM approximation, the double ionization was badly described by classical models. Finally, note that some of the SI and DI results reported in Panels a) and c) have been calculated for liquid water [14] whereas our results concern water vapor.…”
Section: Resultsmentioning
confidence: 91%
“…Whereas our theoretical results exhibit a very good agreement with the recent calculations of Errea et al for describing the CI process [13], we clearly observe an underestimation of the results reported by Gervais et al in [14] (see Panel c)) for the DI process. This large disagreement is actually not well understood but highlights the limitation of the CTMC approach to treat the DI process as already mentioned by Reinhold and Burgdörfer [26] who have shown that in the IEM approximation, the double ionization was badly described by classical models. Finally, note that some of the SI and DI results reported in Panels a) and c) have been calculated for liquid water [14] whereas our results concern water vapor.…”
Section: Resultsmentioning
confidence: 91%
“…In contrast to the perturbation methods, this approach is most applicable when the projectile ion-electron interaction is strong. When this occurs, a very large number of quantum states become populated and their superposition may be successfully mimicked quasi-classically [17]. For weak perturbations, this approach breaks down, as will become clear through the comparisons with experiment and the other theories presented here.…”
Section: Measurementsmentioning
confidence: 88%
“…At intermediate impact velocities this translates into a sizable classical underestimation of the cross sections for emission of electrons into very large, backward, angles. To overcome these classical deficiencies, we present here results of a combined model in which the quantummechanical (B1) results for small momentum transfers are added to the CTMC cross sections [17], which we denote CTMC-I-B1. In this model, we compute the Born approximation limited to momentum transfers Ap, smaller than a critical value given by where Z , is the target nuclear charge and n is the initial electronic principal quantum number, as described in Ref.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1)) that are valid for a limited range of impact parameters and in a second step these approximations should be linked. At large impact parameters the dipole approximation for V i can be used, and thus, an analytical expression [19,20] for Q (b) may be obtained. Inserting the cluster interacting potential, we have, for large impact parameters, an expression of the form…”
Section: Modelmentioning
confidence: 99%